Advancing Sustainability Education and Research at AUB: The Role of ESDU - Lina S. Jaber; Christelle Bou Harb; Diana Marroush; Shady Hamadeh (Journal of Sustainability Perspectives, 2026)
The Environment and Sustainable Development Unit (ESDU) at the American University of Beirut (AUB) has been instrumental in shaping sustainability education through research, interdisciplinary collaboration, and community-driven initiatives. Emerging from an effort to integrate research with real-world development challenges, ESDU fosters partnerships and promotes an applied, participatory approach to learning within and beyond the campus walls. ESDU with other AUB partners has fostered the development of pioneering undergraduate and graduate programs addressing environmental sustainability and management, rural community development, sustainable agriculture, food production, and food security.  In addition to these academic programs that prepare university students to address pressing sustainability challenges through innovative and practical solutions, the ESDU serves as the community engagement arm of the Faculty of Agricultural and Food Sciences  (FAFS) with a major role in capacity building, continuing education and outreach to the community at large with tailored educational and training tools for promoting socioeconomic as well as environmental sustainability at the University and beyond. The ESDU has established a campus-based sustainability show-case, The Urban Oasis; combining top of the line smart technology with traditional material and design it serves as community hub, living-lab in sustainability and an engagement and educational. The role of the ESDU complements the University’s effort towards a more sustainable management of the Institution including collaboration for campus greening and improved waste management. The AUB’s overall sustainability efforts are documented and reported by the Environmental Health, Safety, and Risk Management (EHSRM) department, contributing alongside other university departments to advance institutional sustainability goals).